Metode yanbu‘a dan program tasmi‘ dalam program hafalan al-qur'an pada santri Ponpes An Nur Bantul - Lina Lina; Luluk Latifah; Aris Nurlailiyah (Al Irfani: Journal of Al Qur'anic and Tafsir, 2022)
This research aimed to determine how much influence the learning of the Yanbu'a method and the tasmi' program had on the achievement of memorizing the Qur'an of the students of PP An Nur Bantul Yogyakarta at the Attariq complex. This research used quantitative methods with three variables. The subjects in this research were 40 students. Data collection was done using interviews, documentation, and questionnaires. The instrument validity test was carried out using Aiken's formula and reliability estimation was carried out using Cronbach's Alpha. Data analysis was performed by multiple regression analysis. The results showed that: (1) the Yanbu'a method learning variable (X1) had a positive and significant relationship to the Al-Qur'an memorization achievement variable (Y), which was indicated by the correlation coefficient (Rx1Y) of 0.811, and p (sig) of 0.000. (2) the tasmi' program variable (X2) had a positive and significant relationship to the Al-Qur'an memorization achievement variable (Y). which was indicated by a correlation value (Rx2Y) of 0.821, with a p-value (sig) of 0.000. (3) simultaneously, variables X1 and X2 had an effect of 69.5% on variable Y.